Designing a Sugarcane Based Raw Material Procurement Model for the Sugar Industry - Wahyu Adi Guna; Hartrisari Hardjomidjojo; Marimin Marimin (Jurnal Manajemen Industri dan Logistik, 2026)
This study aims to design a system dynamics model to analyze and improve sugarcane-based procurement at PT Sukses Mantap Sejahtera (PT SMS). The model integrates three subsystems—plantation, production, and demand—to represent the interactions among supply sources, milling capacity, and regional sugar needs. Model validation using Theil's Inequality Statistics confirms the simulation results with actual data, indicating that most deviations arise from random noise rather than systematic bias. Five policy scenarios were designed to enhance system performance: (1) increasing sugarcane prices, (2) introducing subsidies for machinery rental and fertilizers, (3) improving sugarcane yield to 7.68%, (4) expanding livestock routes in the nucleus estate to 210 hectares, and (5) combining Scenarios 2, 3, and 4. Scenario 5 demonstrates the best performance, increasing sugarcane and WCS production by 4.06% and 8.32% annually. By 2030, sugarcane reaches 510,396.56 tons (+6.74%) with 68.05% milling utilization, producing 39,198.46 tons of WCS (+12.14%) and meeting 64.91% of demand in Eastern Indonesia. These results underscore the importance of integrated management, stakeholder collaboration, and Good Agricultural Practices.